Molecular Docking of Compounds in Moringa oleifera Lam with Dipeptidyl Peptidase-4 Receptors as Antidiabetic Candidates - Indah Permata Rendi; Gabriella Josephine Maranata; Hasna Chaerunisa; Nurulita Nugrahaeni; Siti Sarah Alfathonah (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2021)
Background: Diabetes mellitus (DM) type 2 is a metabolic disorder that needs special attention because it can damage several organs if the severity increases. One of the treatments for diabetes mellitus (DM) type 2 is by inhibiting Dipeptidyl peptidase 4 (DPP-IV) with vildagliptin to prolong the hypoglycemic effect of GLP-1 and GIP. Objective: In the search for candidate compounds as new antidiabetic compounds, an in silico test with molecular docking was carried out to predict the antidiabetic activity of 10 Moringa oleifera Lam (MO) plant compounds at the DPP-IV receptor (PDB ID: 6B1E). Method: The study was conducted using the molecular docking method. Result: Validation of the vildagliptin DPP-IV ligand obtained free energy values of -9.27 kcal/mol and RMSD 1.49 í… (RMSD < 2 í…), then tested with 10 test compounds obtained 8 test compounds that have the potential to be antidiabetic. Conclusion: Serpentine compounds have better potential as an antidiabetic drug than other target compounds because they have the closest Gibbs energy (âˆ†G) value to the natural ligand of Vidaglibtin, which is -7.90 kcal/mol. This value is still lower than the free energy of vildagliptin, which is -9.37 kcal/mol. Therefore further testing is needed to ensure the potential of the compound as a candidate for antidiabetic drugs.